Influences of Filled Argon Gas Pressure upon Fluorescent Lamps - Tanaka, Seiichi; Kanaoka, Koji; Matsumoto, Koichiro (Journal of the Illuminating Engineering Institute of Japan, 1955)
Fluorescent lamp is a sort of gas filled oxide coated cathode discharge lamps. Therfore, characteristics of voltage against current of fluorescent lamp are subject to filled Argon gas pressure. Moreover, filled pressure affects evaporation and sputtering of coated oxide, and has influence over the lamp absolute life. When, producing fluorescent lamps, filled Argon gas pressure should have the value to satisfy its necessary conditions. Accordingly, in connection with quality control, manufacturer must establish simple gas pressure measuring method. This report expresses the experimental data on the above requirement. 1) At the definite pressure of filled Argon gas, fluorescent lamp has minimum voltage and minimum gradient of curve of voltage against current. 2) The higher the pressure of filled Argon gas is, the longer the absolute life of fluorescent lamp is. But, for higher efficiency and lower starting voltage, lamp must have lower gas pressure. Accordingly, the lamp must be filled with the definite Argon gas having medium pressure. 3) The characteristics of voltage against current vary according to burning hour. 4) Simple measuring methods of filled Argon gas pressure are as follows: a) The method based upon characteristics of voltage against current. b) The method based upon discharge wave form. c) The method based upon pattern for electrodeless discharge.